1989
DOI: 10.1099/00207713-39-2-100
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Bifunctional Tryptophan Pathway Enzyme for the Classification of the Herbicola-Agglomerans Complex of Bacteria

Abstract: showed that the type strains of Enterobacter agglomerans (ATCC 27155) and Envinia herbicola (ATCC 33243) belong to the same genomic species. We suggest that Enterobacter agglomerans (= Erwinia herbicola) should be excluded from the genus Enterobucter. We further suggest that strains currently designated Enterobacter agglomerans can be grouped with Erwinia herbicola or with the enteric cluster containing Enterobacter depending upon whether bifunctional AS:PRT is absent or present, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Enterocluster 1. Members of enterocluster 1 share a common bifunctional anthranilate synthase:anthranilate 5-phosphoribosylpyrophosphate phosphoribosyltransferase (AS: PRT) gene product of the trpG-trpD fusion (8,37). Two subgroups are proposed: one contains Escherichia, Shigella, Citrobacter and Salmonella; the other contains Klebsiella and Enterobacter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterocluster 1. Members of enterocluster 1 share a common bifunctional anthranilate synthase:anthranilate 5-phosphoribosylpyrophosphate phosphoribosyltransferase (AS: PRT) gene product of the trpG-trpD fusion (8,37). Two subgroups are proposed: one contains Escherichia, Shigella, Citrobacter and Salmonella; the other contains Klebsiella and Enterobacter.…”
Section: Resultsmentioning
confidence: 99%
“…(4,8, 22,36,37), and Fig. 1A shows Serratia to be closer to Klebsiella than Klebsiella is to Salmonella, a result that is at variance with those shown in Fig.…”
mentioning
confidence: 80%
“…Jensen and Ahmad (1,41) proposed that a series of nested gene fusions could be exploited as markers of phylogenetic branch points in prokaryotes. Thus, any organism that belongs to the enteric lineage (shaded green in Fig.…”
Section: Nested Gene Fusionsmentioning
confidence: 99%
“…The trees show the branching order rather than the actual distances. terial groups that diverged at almost the same time; amino acid sequence homologies, for other proteins that are not so highly conserved, and gene-fusion events may be more appropriate methods (Ahmad & Jensen, 1989;Jensen & Ahmad, 1990). Furthermore, a study based on a very small number of genes could give misleading results if one of the genes had been horizontally transferred across bacterial groups at an earlier stage of divergence.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the resolution power of rRNA sequences Is limited when closely related organisms that diverged at almost the same time are being Falah & Gupta, 1994; Gupta, 1995;Gupta & Golding, 1993;Gupta et a/., 1989). These analyses have revealed a number of important differences relative to rRNA-based phylogenies (Boorstein et al, 1994;Brown et al, 1994;Gupta & Golding, 1993 terial groups that diverged at almost the same time; amino acid sequence homologies, for other proteins that are not so highly conserved, and gene-fusion events may be more appropriate methods (Ahmad & Jensen, 1989; Jensen & Ahmad, 1990). Furthermore, a study based on a very small number of genes could give misleading results if one of the genes had been horizontally transferred across bacterial groups at an earlier stage of divergence.…”
mentioning
confidence: 99%